Formation of Highly Misoriented Fragments at Hot Band Grain Boundaries During Cold Rolling of Interstitial-Free Steel - Afrin, N.; Quadir, Md Zakaria; Ferry, M. (2015)
The deformation heterogeneities that form in the vicinity of prior hot band grain boundaries in a 75 pct cold-rolled interstitial-free steel have been investigated by 3D electron backscatter diffraction. Grain boundary-affected regions occupy a large fraction of the overall material volume. The coexistence of several features, such as steep orientation gradients up to 5 deg/µm, high-angle boundary networks, and thin, elongated grain boundary fragments, has confirmed the highly complex nature of these regions. Most notably, these thin boundary fragments were found to be significantly misoriented from any of the deformed grains immediately adjacent to the boundary. Overall, grain boundary regions adopt the so-called ‘deformation banding’ mode of deformations on both the micro (e.g., steep gradients)- and nano (e.g., thin fragments)-length scales. Grain boundary structures comprise the essential features to act as preferred sites for recrystallization. The discovery of numerous thin grain boundary fragments in the deformation microstructure provides a plausible explanation for the origin of recrystallized grains with orientations other than those found within the adjoining deformed grains in the vicinity of grain boundaries; this phenomenon has been commonly observed in texture data for many years but remained unexplained.